Microalgal polyunsaturated fatty acids: Hotspots and production techniques - Chen, Weixian; Li, Tianpei; Du, Shuwen; Chen, Hui; Wang, Qiang (Frontiers in Bioengineering and Biotechnology, 2023)
Algae play a crucial role in the earth’s primary productivity by producing not only oxygen but also a variety of high-value nutrients. One such nutrient is polyunsaturated fatty acids (PUFAs), which are accumulated in many algae and can be consumed by animals through the food chain and eventually by humans. Omega-3 and omega-6 PUFAs are essential nutrients for human and animal health. However, compared with plants and aquatic sourced PUFA, the production of PUFA-rich oil from microalgae is still in the early stages of exploration. This study has collected recent reports on algae-based PUFA production and analyzed related research hotspots and directions, including algae cultivation, lipids extraction, lipids purification, and PUFA enrichment processes. The entire technological process for the extraction, purification and enrichment of PUFA oils from algae is systemically summarized in this review, providing important guidance and technical reference for scientific research and industrialization of algae-based PUFA production.